Hemoroid Interna Grade III Pada Pasien Laki-Laki Usia 49 Tahun - Muhammad Sayuti; Yolanda Restiani (STIKes Ibnu Sina Ajibarang, 2023)
Hemorrhoids are swellings of tissue containing veins located in the walls of the rectum and anus. Mass or bulge in the anal area accompanied by anal bleeding is the main symptom. Proper diagnosis and management of hemorrhoids is very important to reduce morbidity and improve the patient's quality of life. This case report was obtained from primary data through history taking, physical examination and supporting examination. The patient complains of a lump in the anus accompanied by bloody stools since 5 years. Initially the lump came out if the patient strained and could still go in on its own if the patient was not straining anymore. But since 1 year, the lump can't go in on its own, but must be helped to push it with a finger. Heavy bleeding from the anus since 2 months ago. On physical examination the rectal toucher found: good anal sphincter tone, palpable mass with a flat surface, solid, chewy consistency, reddish color, firm boundaries, tenderness (+), lumps can be inserted with fingers, blood on gloves (-), mucus (-), feces (-). Colonoscopy examination revealed grade III internal hemorrhoids. The treatment is hemorrhoidectomy.